Characterization of Leakage and Reliability of SiNx Gate Dielectric by Low-Pressure Chemical Vapor Deposition for GaN-based MIS-HEMTs - Mengyuan Hua; Cheng Liu; Shu Yang; Shenghou Liu; Kai Fu; Zhihua Dong; Yong Cai; Baoshun Zhang; Chen, Kevin J. (IEEE transactions on electron devices, 2015)
In this paper, we systematically investigated the leakage and breakdown mechanisms of the low-pressure chemical vapor deposition (LPCVD) silicon nitride thin film deposited on AlGaN/GaN heterostructures. The LPCVD-SiN x gate dielectric exhibits low leakage and high breakdown electric field. The dominant mechanism of the leakage current through LPCVD-SiN x gate dielectric is identified to be Poole-Frenkel emission at low electric field and Fowler-Nordheim tunneling at high electric field. Both electric-field-accelerated and temperature-accelerated time-dependent dielectric breakdown of the LPCVD-SiN x gate dielectric were also investigated.